Evaluation of the Validity and Reliability of a Therapeutic Communication Questionnaire Instrument for Cancer Patients - Rahmawati, Afrianka; Rosyad, Yafi Sabila (Holistic Nursing Plus, 2025)
This study aims to examine the validity and reliability of a therapeutic communication questionnaire used with cancer patients undergoing chemotherapy. Therapeutic communication is a crucial element in patient recovery and an integral part of nursing practice. A quantitative approach with a descriptive correlational design was applied, involving 100 patients at RSPAU Dr. S. Hardjolukito, Yogyakarta. The instrument consisted of 20 items adapted from Rizky Hardhiyani (2013). Validity testing showed that all items had a correlation coefficient (r) greater than the critical value (0.196), ranging from 0.203 to 0.412, and were therefore deemed valid. Reliability testing yielded a Cronbach's Alpha value of 0.663, meeting the minimum reliability threshold (>0.60). Thus, this questionnaire is considered a valid and reliable instrument for assessing therapeutic communication in cancer patients.